The operational matrices of Bernstein polynomials for solving the parabolic equation subject to specification of the mass - Yousefi, S.A.; Behroozifar, M.; Dehghan, Mehdi (Journal of computational and applied mathematics, 2011)
Some physical problems in science and engineering are modelled by the parabolic partial differential equations with nonlocal boundary specifications. In this paper, a numerical method which employs the Bernstein polynomials basis is implemented to give the approximate solution of a parabolic partial differential equation with boundary integral conditions. The properties of Bernstein polynomials, and the operational matrices for integration, differentiation and the product are introduced and are utilized to reduce the solution of the given parabolic partial differential equation to the solution of algebraic equations. Illustrative examples are included to demonstrate the validity and applicability of the new technique. ► A discrete complex-valued bidirectional associative memory network is considered. ► Sufficient condition is given for stored patterns to be fixed points of the network. ► Each fixed point is shown to belong to a fixed point group of four fixed points.